Travma Sonrası Süreğen Şiddetli Başağrısı: Postkonküzyon Sendromlu Bir Ergen - (:unkn) unknown (My University, 2016)
Postkonküzyon sendromu (PKS) genellikle hafif şiddette kafa travmaları sonrası oluşmakla birlikte orta şiddette kafa travmaları sonucu da oluşabilir. PKS, fiziksel, psikiyatrik (duygusal ve davranışsal) ve bilişsel yetersizlik belirtileri gösterebilmekte ve bu hastalar 3-6 ay arasında %10'u hariç tamamen iyileşmektedir. PKS'li hastalar, başlangıçta hayati olarak ağır belirtiler göstermekte iken trajik bir şekilde iyileşmektedirler. Yüksekten düşme sonucu kafa travması yaşayan, 18 gün yoğun bakım tedavisi alan ve dramatik iyileşme belirtileri gösteren olguyu paylaşmadaki amacımız; olumsuz hayat olayları ile ilişkilendirilebilecek gibi görünen psikiyatrik bulguların ve travma sonrası şiddetli ve tedaviye dirençli başağrısı tablosunun bütüncül olarak ele alındığında aslında PKS'nin bileşenleri olabileceği durumuna dikkat çekmektir.

Post-concussion syndrome (PCS), apart from occurring in the wake of mild traumatic brain injuries (TBIs) in general, may also occur as the result of moderate TBIs. PCS patients may exhibit symptoms of physical, psychiatric (emotional and behavioral) and cognitive inabilities. Patients, except for the 10%, make a full recovery between 3-6 months. While patients with PCS show vitally acute symptoms at the outset, the clinical recovery is dramatically good. A fifteen-year-old female patient who had undergone a head trauma as the result of falling down from height showed a clinically dramatic recovery after an 18-day-treatment of intensive care. We aimed to draw the attention to the association between the psychiatric findings that appeared to be likely to be associated with negative life events and the clinical picture of a post-traumatic severe headache resistant to treatment. This clinical picture, when dealt with the holistic multidisciplinary approach, may indicate PCS to us.
Posttraumatic Severe Chronic Headache: An Adolescent with Postconcussion Syndrome
Keywords: Cerrahi